Dependence of the synthetic strategy on the thermochemical energy storage capability of CuxCo3-xO4 spinels. Issue 4 (April 2018) - Tamayo, A.; Rodríguez, MªA.; Arroyo, C.; Beltran-Heredia, J.; Rubio, F.
Abstract: Cux Co3-x O4 spinels have been prepared through three different synthetic approaches to obtain oxide materials where the cationic distribution along the octahedral and tetrahedral sites is modified. The correlation of the spectroscopic characterization techniques and XRD patterns allowed to identify the relative concentration of the cationic species in the coordination environments. The aqueous routes favor the intimate contact of the cations and then, the migration of Co(III) to a tetrahedral coordination with Cu incorporation is promoted. This conversion to a partially inverse spinel structure leads to a decrease of the thermochemical capability of the prepared materials, in terms of energy balance but the O2 release from the structure is favored with the increase in the number of cations occupying the tetrahedral sites. The endothermic reaction associated to the redox transition to CoO occurs in two differentiated steps which can be correlated with the degree of the inversion of the spinel structure.